PSYCHOLOGICAL FACTORS ON STUDENT SPEAKING ENGLISH PROBLEMS AT SMAN 6 TAMBUN SELATAN - Siti Fauziyah; Roslaini Roslaini (Al-Irsyad: Journal of Education Science, 2025)
The research was conducted to thoroughly explore the barriers that hinder students' ability to learn effectively, both from psychological and academic perspectives. Previous studies on English learning difficulties have primarily focused on linguistic and academic factors, such as grammar mastery, vocabulary development, and reading or writing skills. However, limited attention has been given to the psychological barriers that significantly influence students' ability to learn and perform in English, particularly in the context of Indonesian high school students. While some research has mentioned issues like anxiety or fear of making mistakes, these studies often lack a detailed exploration of how psychological factors interact with academic challenges to affect students' confidence and participation in class. This study aims to address this gap by thoroughly investigating both psychological and academic barriers that hinder students' English learning process. By using a questionnaire distributed to students at SMAN 6 Tambun Selatan, the research highlights the dominant role of fear and anxiety as emotional obstacles that reduce students' self-confidence and willingness to engage in learning activities. The findings emphasize the importance of creating supportive and anxiety-reducing classroom environments, which have not been adequately discussed in prior research.